The influence of price presentation (in audio format) on customers perceptions - Rodrigues, Hugo Leonardo; Mainardes, Emerson Wagner (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This study sought to verify the impacts on people’s perception from using the digit “9” in the price format (in audio mode). The research was conducted in three experiments, in each of which respondents were divided into two groups, each with an audio offer and with a different price format (either with or without the digit “9” in the offer). The samples were similar to each other. As analytical tools we used Student’s t-tests, which in general showed that the use of the digit “9” in the price format can impact customers’ perception about price evaluation, deal evaluation, purchase intent, advertising evaluation, store referral, assessment of cost–benefit relations and evaluation of the advertising format.